Penguatan Konsep Sistem Pendengaran, Pembau, dan Perasa pada Komunitas Guru Biologi Sidoarjo - Adrianto, Hebert; Santoso, Jemima Lewi; Tantana, Olivia; Rahayu, Novi Widia; Themone, Anacy Simproza Melania; Laila, Najmul (Universitas Ekuitas Indonesia, 2024)
The hearing, smell, and taste systems are important parts of humans because they function to respond to the surrounding environment. People of all ages often ignore ear hygiene and health. Nasal disorders are a disease that is often found in society. The community service activities were attended by high school biology teachers in Sidoarjo City. This activity is based on the results of observations with partners about learning needs and learning topics that are considered difficult by the teacher. Teachers have a role in forming good and healthy behavior for students. This community service aims to reinforce biological material concepts on the topic of hearing, smell, and taste systems to high school Biology MGMP teachers. The way to carry out community service is in the form of concept imposition. Activity stages include pre-activity, during-activity, and post-activity. The concepts given to participants are the hearing, smell, and taste systems. The results of the activity include participants taking part in the activity during three face-to-face meetings. The first meeting used Zoom. The second and third meetings were at the school. The participant with the high score gets the Human Ear Anatomy Model. There was an increase in the post-test score compared to the pre-test score after participants followed the material with the resource person, amounting to 33.53% at the first meeting and 89.42% at the second meeting. This activity can be held again through a laboratory practicum and experience-based learning for the next project. Keyword: Teacher, Biology, Ear, Nose, Tongue Abstrak Sistem pendengaran, pembau, dan perasa merupakan salah satu indera penting pada manusia yang berfungsi untuk merespon lingkungan di sekitarnya. Masyarakat segala umur sering mengabaikan kebersihan dan kesehatan telinga. Gangguan penyakit pada hidung adalah penyakit yang sering dijumpai di masyarakat. Kegiatan ini didasari hasil observasi dengan mitra kebutuhan belajar dan topik belajar yang dianggap sulit oleh guru. Guru memiliki peran membentuk perilaku baik dan sehat kepada siswa. Pengabdian masyarakat ini bertujuan untuk memberikan penguatan konsep materi biologi topik sistem pendengaran, pembau, dan perasa kepada MGMP Biologi Sidoarjo. Metode pelaksanaan pengabdian masyarakat berupa penguatan konsep. Kegiatan dilaksanakan pada guru biologi di Sekolah Menengah Atas di Sidoarjo. Tahapan kegiatan meliputi pra-kegiatan, saat kegiatan, dan pasca kegiatan. Konsep yang diberikan kepada peserta adalah sistem pendengaran, pembau, dan perasa. Hasil kegiatan meliputi peserta mengikuti kegiatan selama tiga kali tatap muka. Pertemuan pertama dilaksanakan secara online dengan zoom. Pertemuan kedua dilaksanakan secara offline di sekolah. Peserta dengan nilai terbaik mendapatkan souvenir berupa torso sistem indera telinga. Ada peningkatan nilai post-test dibandingkan nilai pre-test setelah peserta mengikuti materi dengan narasumber, sebesar 33,53% pada pertemuan pertama dan 89,42% pada pertemuan kedua. Kegiatan ini dapat diadakan kembali dengan praktikum laboratorium dan pembelajaran berbasis pengalaman untuk kegiatan selanjutnya. Kata kunci: Guru, Biologi, Telinga, Hidung, Lidah